Making equal : new visions for opportunity and growth - Atherton, Graeme; John, Peter (Emerald Publishing Limited, 2025)
Presenting new, challenging solutions to the severe problem of inequality in the UK, Making Equal brings together a wide range of senior respective figures across the fields of politics, academia and the voluntary sector to outline their visions of how a less unequal Britain could be created and why doing so now is an economic and moral imperative for the nation. Ideas outlining how welfare, the criminal justice system, education and skills, the regional distribution of power and how the economy itself needs to be rewired, are presented by ex-Ministers, academics, university leaders and heads of charities. The chapter authors analyse the extent of social and economic inequality in the UK, critique present approaches to addressing inequality and identify key principles, a future research agenda and an over-arching policy approach to addressing inequality and its consequences. The chapters are drawn in the main from contributions to the Ruskin College, Oxford Seminar Series and Making Equal celebrates the 125th anniversary of the formation of the college. Transcending disciplines and bringing together a range of diverse experts, Making Equal is a valuable resource for anyone interested in understanding and addressing inequality in the UK.